THE EFFECT OF HEALTH EDUCATION TOWARD KNOWLEDGE OF THE ELDERLY IN MANAGEMENT RISK OF URINARY INCONTINENCE - Reni Devita (Universitas Batanghari Jambi, 2018)
One important means on the Management of human resources in a organization is the creation of job satisfaction of employees. Job satisfaction is an individual attitude, the greater aspects of the work in accordance with the wishes and goals, the higher the perceived level. Based on the above, the authors are interested in making the study titled